Preparation method and application of composite particles for extracting cesium and uranium
By loading ammonium phosphomolybdate (AMP) to a magnetic iron tetraoxide (Fe3O4) carrier and forming a polydopamine (PDA) coating composite material, the problem of low removal efficiency of Cs and U in seawater is solved, and the effect of efficient adsorption and easy recovery is achieved.
Patent Information
- Application Number
- CN202211598249.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-12-14
AI Technical Summary
The prior art is difficult to efficiently remove long-lived radionuclides Cs and U in seawater, especially under the interference of high impurity ions. Traditional methods such as membrane filtration, precipitation and adsorption separation have problems such as low efficiency and easy material loss.
Using AMP@PDA@Fe3O4 composite material, the composite material can efficiently adsorb Cs and U under the interference of high impurity ions by loading ammonium phosphomolybdate (AMP) onto a magnetic iron tritetroxide (Fe3O4) carrier and forming a polydopamine (PDA) coating on its surface.
It realizes efficient adsorption of Cs and U in seawater, and due to the magnetic properties of Fe3O4 carrier, the material is easy to recover and avoids secondary pollution. At the same time, the polydopamine coating improves the hydrophilicity and adsorption efficiency of the material.
Smart Images

Figure CN116037077B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal extraction, and in particular to a preparation method and application of composite particles for extracting cesium and uranium. Background Art
[0002] With the increase in global energy demand and the continued consumption of fossil fuels and other non-renewable resources, countries are vigorously developing nuclear energy to solve the problem of energy shortage. Nuclear power generation is huge in scale, and the safe treatment of wastewater related to nuclear industry production is receiving more and more attention. Especially in nuclear leakage incidents occurring in the ocean, due to the contact between cooling water and nuclear fuel fragments, a large amount of radioactive wastewater accumulates in reactors, turbine plants and tunnels, threatening the safety and health of all mankind and the world environment. According to investigations, after a nuclear accident, a large number of long-lived radioactive nuclides can be detected in residential areas near the accident. 238 U(VI), 137 Cs(I), 129 I(I)and 90 Sr(II). Compared with other radionuclides, Cs(I) and U(VI) are more difficult to remove because they can exist stably in water, have high mobility and extremely long half-life. Some physical and chemical properties of Cs are very similar to those of K and Na in the same main group. They are easily integrated into the food chain and accumulated in the human body, and then induce β-decay, leading to serious health diseases such as cancer, tumors, genetic diseases, organ system failure, bone dysfunction and reproductive problems. At the same time, radioactive U will continuously release rays such as α, γ and β through its own decay. When the human body and organisms are exposed to high doses of radiation, their tissues and organs will be damaged to varying degrees, or even die directly. Therefore, the removal of long-term radionuclides Cs and U from nuclear wastewater has become an important environmental issue. Membrane filtration, precipitation, solvent extraction, electrocoagulation, adsorption separation and other methods are commonly used to remove cesium and uranium. In recent years, adsorption separation has attracted attention due to its simple operation mode, cheap equipment, high selectivity and high efficiency.
[0003] Studies have shown that ammonium phosphomolybdate (AMP, (NH4)3PMo 12 O 40 ) is a heteropolyacid salt with Keggin structure, NH4 + and H2O molecules fill the crystal gaps, of which NH4 + With Cs +It has a good exchange effect. Because of its large adsorption capacity and high adsorption efficiency, it is considered to be an ideal ion exchange material. However, the commercially available AMP has a microcrystalline structure (about 1nm) and is easily reduced to phosphomolybdenum blue. The filling column filled with AMP alone has poor water permeability and is easily lost during the adsorption process, causing secondary pollution. The existing APM / SiO2 nanocomposite synthesized by loading ammonium phosphomolybdate on a silica carrier still needs to be separated from the water body by long-term natural sedimentation or centrifugation. The present invention intends to utilize the advantage of AMP's efficient adsorption of cesium to load AMP onto a suitable carrier, thereby solving the problem of removing Cs and U in radioactive wastewater. Summary of the invention
[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a preparation method and application of composite particles for extracting cesium and uranium.
[0005] The purpose of the present invention is achieved by the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing composite particles for extracting cesium and uranium, comprising the following steps:
[0007] (1) Synthesis of large hollow iron oxide core particles:
[0008] S1. Disperse FeCl3·6H2O in ethylene glycol, and after fully dissolving, add NaAc and sodium dodecyl sulfate, and fully dissolve again to form a reactant solution;
[0009] S2. The reactant solution was transferred to a reactor for hydrothermal reaction. After cooling, the obtained black powder was separated by magnetic separation, washed alternately with pure water and alcohol three times, and dried with a vacuum freeze dryer to obtain large-particle hollow ferroferric oxide cores;
[0010] (2) Synthesis of AMP@PDA@Fe3O4 composite materials:
[0011] S3. The hollow ferroferric oxide core, ammonium phosphomolybdate particles and dopamine hydrochloride were mixed, ultrapure water was added, and the mixture was stirred thoroughly to obtain a mixed suspension solution A. The pH was adjusted to 8.5, and then the suspension was ultrasonicated and mechanically stirred at room temperature. After magnetic separation, the suspension was washed alternately with pure water and alcohol for three times, and dried with a vacuum freeze dryer to obtain an AMP@PDA@Fe3O4 composite material (APF).
[0012] Preferably, in step (1), the diameter of the core of the obtained large-particle hollow ferroferric oxide is 100 nm.
[0013] Preferably, in step (1), the solid-to-liquid ratio of FeCl3·6H2O to ethylene glycol is 4.05 g:60 mL.
[0014] Preferably, in step (1), the mass ratio of NaAc to sodium dodecyl sulfate is 4.07:0.46.
[0015] Preferably, in step (1), the re-dissolving is performed by stirring in a water bath at 50° C. for 60 min.
[0016] Preferably, in step (1), the hydrothermal reaction is carried out at 200° C. for 12 hours.
[0017] Preferably, in step (2), the mass ratio of ammonium phosphomolybdate, dopamine hydrochloride and hollow ferrosoferric oxide core is 10-40:5-20:40-85.
[0018] Preferably, in step (2), the ratio of the added mass of ultrapure water to the total mass of solids is 100:1.
[0019] Preferably, in step (2), the pH of solution A is adjusted to 8.5 with a Tris-HCl buffer solution, followed by ultrasonication for 30 min, and then mechanical stirring at a speed of 420 r / min for 24 h at room temperature.
[0020] In a second aspect, the present invention provides an application of composite particles for extracting cesium and uranium. The composite particles obtained by the above preparation method are applied to extracting cesium and uranium from seawater.
[0021] The beneficial effects of the present invention are:
[0022] 1. In the present invention, a composite particle that can be used to extract cesium and uranium from seawater is prepared. The composite particle is an AMP@PDA@Fe3O4 composite material. The composite material retains the AMP property and can efficiently adsorb Cs(I) in seawater under the interference of high impurity ions; in addition, the composite material also has the PDA property and can efficiently adsorb U(VI) in seawater under the interference of high impurity ions.
[0023] 2. The present invention can solve the shortcoming of AMP being easy to lose and load it onto a Fe3O4 carrier, making it magnetic and easy to recover. At the same time, since the polydopamine coating is loaded on the Fe3O4 carrier, it has hydrophilicity, which is beneficial to the dispersion of the material in water and the adsorption of uranium.
[0024] 3. In the AMP@PDA@Fe3O4 composite material prepared by the present invention, dopamine forms a polymer while solid particles such as ammonium phosphomolybdate microcrystalline particles (including but not limited to ammonium phosphotungstate and other similar particles) can be attached to the surface of the Fe3O4 carrier in the polydopamine coating by embedding. The performance of the ammonium phosphomolybdate-polydopamine coating can also be determined according to the different addition amounts of dopamine and ammonium phosphomolybdate. By adjusting the ratio of ammonium phosphomolybdate and the ratio of polydopamine, cesium and uranium can be removed more efficiently. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.
[0026] Figure 1 This is a flow chart of the steps for synthesizing AMP@PDA@Fe3O4 material in Example 1 of the present invention;
[0027] Figure 2 In the figure, scanning transmission electron microscopy of Fe3O4 (a); scanning transmission electron microscopy of AMP@PDA@Fe3O4 material (b) and high-resolution transmission electron microscopy of AMP@PDA@Fe3O4 material (c). DETAILED DESCRIPTION
[0028] In order to more clearly illustrate the present invention and have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0029] The present invention utilizes the advantage of AMP's high efficiency in adsorbing cesium to modify it, and preferably loads AMP onto a suitable carrier. The Fe3O4 particles are magnetic, and preferably the carrier modified by AMP. At the same time, studies have shown that Fe3O4 has an adsorption effect on U(VI). However, due to the strong magnetism of Fe3O4, it will attract each other during the adsorption process, reducing the adsorption rate. Therefore, by establishing some functional chemical or physical coatings on its surface, its performance can be improved while maintaining the magnetic separation function.
[0030] Polydopamine (PDA) is a biocompatible biomimetic polymer that can form a stable coating on almost any material (including hydrophobic surfaces) and change its surface to hydrophilic. Dopamine (DA) forms PDA through self-polymerization and electrostatic interaction at pH 8.5. The structure of PDA is very complex and consists of oligomers of dopamine oxidation products. Studies have shown that PDA has an adsorption effect on U(VI) and is suitable for AMP and Fe3O4 modified coatings.
[0031] Therefore, the present invention is suitable for preparing AMP@PDA@Fe3O4 composite materials to solve the problem of removing Cs and U in radioactive wastewater.
[0032] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0033] The present invention is further described in conjunction with the following examples.
[0034] Example 1
[0035] A method for preparing particles of ammonium phosphomolybdate ferroferric oxide complex for extracting cesium and uranium from seawater comprises the following steps:
[0036] (1) Synthesize large-particle hollow Fe3O4 core with a diameter of about 100 nm.
[0037] Disperse 4.05g FeCl3·6H2O in 60ml ethylene glycol, add 4.07g NaAc and 0.46g sodium dodecyl sulfate after fully dissolving, and stir in a 50℃ water bath for 60min until fully dissolved. Transfer the above liquid to a 200ml reactor, react at 200℃ for 12 hours, cool, separate the obtained black powder by magnetic separation, wash it alternately with pure water and alcohol for 3 times, and dry it with a vacuum freeze dryer to obtain hollow ferroferric oxide nanoparticles with a diameter of about 100nm.
[0038] (2) Synthesis of AMP@PDA@Fe3O4 composite materials.
[0039] The synthesized ferroferric oxide nanoparticles and commercially purchased ammonium phosphomolybdate particles, as well as dopamine hydrochloride, were mixed in a certain ratio (ammonium phosphomolybdate: dopamine hydrochloride: ferroferric oxide = 10-40wt. %: 5-20wt. %: 40-85wt. %), and then added with up water (solid-liquid ratio of 1g: 100ml) to form a suspension solution A. The pH of solution A was adjusted to 8.5 with Tris-HCl buffer solution and then ultrasonicated for 30 minutes. Solution A was then placed under mechanical stirring at 420r / min at room temperature for 24 hours, and after magnetic separation, it was washed alternately with pure water and alcohol for 3 times, and dried with a vacuum freeze dryer to obtain AMP@PDA@Fe3O4 composite material (named APF).
[0040] Example 2
[0041] During the synthesis of the APF material using the method of Example 1, the mass fraction of dopamine input in the composite material was fixed at 5 wt.%, and the content of ammonium phosphomolybdate was adjusted to 10 wt.%. The synthesized APF material was named 10-5APF.
[0042] Example 3
[0043] During the synthesis of the APF material using the method of Example 1, the mass fraction of dopamine input in the composite material was fixed at 5 wt.%, and the content of ammonium phosphomolybdate was adjusted to 20 wt.%. The synthesized APF material was named 20-5APF.
[0044] Example 4
[0045] During the synthesis of the APF material using the method of Example 1, the mass fraction of dopamine input in the composite material was fixed at 5 wt.%, and the content of ammonium phosphomolybdate was adjusted to 30 wt.%. The synthesized APF material was named 30-5APF.
[0046] Example 5
[0047] During the synthesis of the APF material using the method of Example 1, the mass fraction of dopamine input in the composite material was fixed at 5 wt.%, the content of ammonium phosphomolybdate was adjusted to 40 wt.%, and the synthesized APF material was named 40-5APF.
[0048] Experimental Example 1
[0049] The APF material prepared in Example 2-5 was used to adsorb 20 ppm of cesium at a dosage of 1 g / L, and different adsorption rates and equilibrium times were obtained, as shown in Table 1.
[0050] Among them, it can be seen from Table 1 that the adsorption rate of 40-5APF material can reach 99.88%, and the adsorption equilibrium time is 30 minutes.
[0051] Table 1 Adsorption of 20ppm cesium by different APF materials
[0052]
[0053] Experimental Example 2
[0054] The material 40-5APF was selected to adsorb 20ppm of cesium at a dosage of 0.5g / L under the condition of pH 3 to 11. The adsorption performance of 40-5APF was the best at pH = 6, and the adsorption capacity reached 35.25mg / g. Under other pH conditions, the adsorption capacity of material 40-5APF for cesium could reach more than 31.01mg / g.
[0055] Experimental Example 3
[0056] Different APF materials were used to adsorb 10ppm uranium (VI) at a dosage of 1g / L, and different adsorption rates and equilibrium times were obtained, as shown in Table 2. Among them, the adsorption rates of 40-5, 40-10 and 40-15 APF materials for 10ppm uranium (VI) were 84.45%, 98.39% and 99.70% respectively, with high removal rates. The adsorption rate increased with the increase of the mass fraction of dopamine.
[0057] Table 2 Adsorption of 10ppm uranium by different APF materials
[0058]
[0059] Example 4
[0060] The material 40-10APF was selected to adsorb 10 ppm of uranium (VI) at a dosage of 0.5 g / L under the condition of pH 3 to 9. When pH = 5 to 7, 40-15APF had a better uranium adsorption performance, and the efficiency of uranium adsorption could reach 85.87% when pH = 7.
[0061] Example 5
[0062] The material 40-10APF was selected with a dosage of 1.0 g / L, and the pollutants were added to real seawater, and the pH was adjusted to 6. The adsorption rates of cesium and uranium in seawater can reach 97.65% and 84.63% respectively. The main components of each element in seawater are shown in Table 3.
[0063] Table 3 Element composition and removal rate of seawater simulating marine uranium-cesium contamination
[0064] element Initial concentration (mg / L) Adsorption rate (%) Na 6674.6 14.18 Mg 851.2 14.10 Al 1582.8 14.44 K 460.1 13.26 Ca 402.1 5.42 Br 93.1 13.67 Sr 13.5 14.61 Cs 17.7 97.65 U 16.4 84.63
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing composite particles for extracting cesium and uranium, characterized in that: The following steps are involved: (1) Synthesis of large hollow iron oxide core particles: S1. Disperse FeCl3·6H2O in ethylene glycol, and after fully dissolving, add NaAc and sodium dodecyl sulfate, and fully dissolve again to form a reactant solution; S2. The reactant solution was transferred to a reactor for hydrothermal reaction. After cooling, the obtained black powder was separated by magnetic separation, washed alternately with pure water and alcohol three times, and dried with a vacuum freeze dryer to obtain large-particle hollow ferroferric oxide cores; (2) Synthesis of AMP@PDA@Fe3O4 composite materials: S3. The hollow ferroferric oxide core, ammonium phosphomolybdate particles and dopamine hydrochloride were mixed, ultrapure water was added, and the mixture was stirred thoroughly to obtain a mixed suspension solution A. The pH was adjusted to 8.5, ultrasonicated, mechanically stirred at room temperature, and magnetically separated. The mixture was washed alternately with pure water and alcohol for 3 times, and dried with a vacuum freeze dryer to obtain an AMP@PDA@Fe3O4 composite material. In step (1), the diameter of the core of the obtained large-particle hollow ferroferric oxide is 100 nm; In step (2), the mass ratio of ammonium phosphomolybdate, dopamine hydrochloride and hollow ferrosoferric oxide core is 10-40:5-20:40-85.
2. The method for preparing composite particles for extracting cesium and uranium according to claim 1, characterized in that: In step (1), the solid-liquid ratio of FeCl3·6H2O to ethylene glycol is 4.05 g: 60 mL.
3. The method for preparing composite particles for extracting cesium and uranium according to claim 1, characterized in that: In step (1), the mass ratio of NaAc to sodium dodecyl sulfate is 4.07:0.
46.
4. The method for preparing composite particles for extracting cesium and uranium according to claim 1, characterized in that: In step (1), the solution is fully dissolved again by stirring in a water bath at 50°C for 60 min.
5. The method for preparing composite particles for extracting cesium and uranium according to claim 1, characterized in that: In step (1), the hydrothermal reaction conditions are: reaction at 200° C. for 12 hours.
6. The method for preparing composite particles for extracting cesium and uranium according to claim 1, characterized in that: In step (2), the ratio of the added mass of ultrapure water to the total mass of solids is 100:
1.
7. The method for preparing composite particles for extracting cesium and uranium according to claim 1, characterized in that: In step (2), the pH of solution A was adjusted to 8.5 with a Tris-HCl buffer solution, followed by ultrasonic treatment for 30 min, and then mechanical stirring at 420 r / min for 24 h at room temperature.
8. An application of composite particles for extracting cesium and uranium, characterized in that: The composite particles obtained by the preparation method described in any one of claims 1 to 7 are used for extracting cesium and uranium from seawater.
Citation Information
Patent Citations
Preparation method of porous AMP / CNC-PUF adsorption material and application thereof
CN106975470A